2016
DOI: 10.1103/physreve.93.043120
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent transport with intermittency: Expectation of a scalar concentration

Abstract: Scalar transport by turbulent flows is best described in terms of Lagrangian parcel motions. Here we measure the Eulerian distance travel along Lagrangian trajectories in a simple point vortex flow to determine the probabilistic impulse response function for scalar transport in the absence of molecular diffusion. As expected, the mean squared Eulerian displacement scales ballistically at very short times and diffusively for very long times, with the displacement distribution at any given time approximating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…To study the vertical dispersion of single-particles observed in the DNSs of SST in section III, we now present a stochastic model that combines a random wave model (to consider the effect of internal gravity waves) with a CTRW [35] (to capture the effect of overturning by turbulent or large-scale eddies).…”
Section: Single-particle Vertical Dispersion Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the vertical dispersion of single-particles observed in the DNSs of SST in section III, we now present a stochastic model that combines a random wave model (to consider the effect of internal gravity waves) with a CTRW [35] (to capture the effect of overturning by turbulent or large-scale eddies).…”
Section: Single-particle Vertical Dispersion Modelmentioning
confidence: 99%
“…We also present a model for the vertical single-and two-particle vertical dispersion that is in good agreement with the DNS results. The model consist of a continuous-time random walk (CTRW) based on a previous model for HIT [34,35] (to model trapping of tracers by turbulent eddies, and the effect of local overturning instabilities), and a random superposition of waves, and can capture the vertical dispersion of particles at all times and in all SST regimes considered. The superposition of linear and turbulent effects in the model allows us to identify the leading physical effects resulting in vertical dispersion at early and at late times in the flow (compared with the period of the internal gravity waves).…”
Section: Introductionmentioning
confidence: 99%
“…Since vertical dispersion is small, particle motions in planes perpendicular to the mean stratification can be approximated as two dimensional, and prediction of dispersion in this direction is relevant for the stably stratified atmosphere and for other geophysical flows. Thus, a model for the probability distribution P (x, t; x , t ) of finding a particle at (x, t) given a previous location (x , t ) has multiple applications, and would allow probabilistic prediction of the concentration of quantities transported by the flow without resorting to ensembles of deterministic simulations with small differences in the initial concentrations [27]. In the following we derive a model for this distribution resorting only to general statistical properties of the turbulent flow.…”
Section: Horizontal Dispersionmentioning
confidence: 99%
“…In the latter (transport perpendicular to the stratification), dispersion differs from HIT as it is strongly influenced by the large scale shearing flow generated by the stratification, and which plays an important role in the atmosphere [18][19][20]. The model used in this case is then a continuous-time eddy-constrained (CTEC) random walk (which accounts for particle trapping observed in HIT [27]), with a superposed drift caused by the vertically sheared horizontal winds (VSHW) in stably stratified turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, there was a significant activity devoted to vortex gas modelling of (particularly decaying) 2-D turbulence [20][21][22][23][24], where merging rules for point vortices were prescribed, yielding 2-D turbulence-like behavior at reduced numerical cost. Point vortex models have also been used to investigate stirring by chaotic advection [25], as well as Lagrangian intermittency, pair dispersion and transport in turbulence [26][27][28]. Recently, vortex gas scaling arguments were leveraged to find a highly accurate local closure in baroclinic turbulence [29].…”
Section: Introductionmentioning
confidence: 99%